In vivo sonic hedgehog pathway antagonism temporarily results in ancestral proto-feather-like structures in the chicken. - Rory L Cooper; Michel C Milinkovitch (PLoS Biology)
The morphological intricacies of avian feathers make them an ideal model for investigating embryonic patterning and morphogenesis. In particular, the sonic hedgehog (Shh) pathway is an important mediator of feather outgrowth and branching. However, functional in vivo evidence regarding its role during feather development remains limited. Here, we demonstrate that an intravenous injection of sonidegib, a potent Shh pathway inhibitor, at embryonic day 9 (E9) temporarily produces striped domains (instead of spots) of Shh expression in the skin, arrests morphogenesis, and results in unbranched and non-invaginated feather buds-akin to proto-feathers-in embryos until E14. Although feather morphogenesis partially recovers, hatched treated chickens exhibit naked skin regions with perturbed follicles. Remarkably, these follicles are subsequently reactivated by seven weeks post-hatching. Our RNA-sequencing data and rescue experiment using Shh-agonism confirm that sonidegib specifically down-regulates Shh pathway activity. Overall, we provide functional evidence for the role of the Shh pathway in mediating feather morphogenesis and confirm its role in the evolutionary emergence and diversification of feathers.